Findings from 4C-T study demonstrate an increased cardiovascular burden in girls with end stage kidney disease and kidney transplantation - Sugianto, Rizky; Memaran, Nima; Schmidt, Bernhard M. W.; Doyon, Anke; Thurn-Valsassina, Daniela; Alpay, Harika; Anarat, Ali; Arbeiter, Klaus; Azukaitis, Karolis; Bayazit, Aysun K.; Bulut, Ipek K.; Caliskan, Salim; et al. (Kidney international, 2022)
Mortality in children with kidney failure is higher in girls than boys with cardiovascular complications representing the most common causes of death. Pulse wave velocity (PWV), a measure of vascular stiffness, predicts cardiovascular mortality in adults. Here, PWV in children with kidney failure undergoing kidney replacement therapy was investigated to determine sex differences and potential contributing factors. Two-hundred thirty-five children (80 girls; 34%) undergoing transplantation (150 pre-emptive, 85 with prior dialysis) having at least one PWV measurement pre- and/or post-transplantation from a prospective cohort were analyzed. Longitudinal analyses (median/maximum follow-up time of 6/9 years) were performed for PWV z-scores (PWVz) using linear mixed regression models and further stratified by the categories of time: pre-kidney replacement therapy and post-transplantation. PWVz significantly increased by 0.094 per year and was significantly higher in girls (PWVz +0.295) compared to boys, independent of the underlying kidney disease. During pre-kidney replacement therapy, an average estimated GFR decline of 4 ml/min/1.73 m2 per year was associated with a PWVz increase of 0.16 in girls only. Higher diastolic blood pressure and low density lipoprotein were independently associated with higher PWVz during pre-kidney replacement therapy in both sexes. In girls post-transplantation, an estimated GFR decline of 4ml/min/1.73m2 per year pre-kidney replacement therapy and a longer time (over 12 months) to transplantation were significantly associated with higher PWVz of 0.22 and of 0.57, respectively. PWVz increased further after transplantation and was positively associated with time on dialysis and diastolic blood pressure in both sexes. Thus, our findings demonstrate that girls with advanced chronic kidney disease are more susceptible to develop vascular stiffening compared to boys, this difference persist after transplantation and might contribute to higher mortality rates seen in girls with kidney failure.